Identifying senior high school students' learning styles at a diagnostic assessment - Sofhiya, Evie Nur; Ivo, Diana Pungki Astro; Setyowati, Djiwanti Retno; Febrianti, Novi; Altawil, Abdulmohsin Nasser (Universitas Ahmad Dahlan, 2023)
Learning style can be interpreted as the process of appreciation, behavior, and tendencies of a student in acquiring knowledge. One of the keys to student success in the learning process is that it is influenced by a learning style that suits the students. This research aims to identify the learning styles of class XI students at SMA Negeri 4 Yogyakarta. This research is a type of survey research. The research population was all class XI students at SMA Negeri 4 Yogyakarta. The sample was taken from 72 students from class XI F3, F5, and F6 of SMA Negeri 4 Yogyakarta, which was determined using purposive sampling. Data analysis was carried out descriptively presenting the results obtained from closed questionnaires. The overall results obtained in this study show a kinesthetic learning style with a percentage of 36.1%. Class F3 tends to be kinesthetic and F5 and F6 tend to be visual.